Alienation or Cooperation? British Muslims’ Attitudes to and Engagement in Counter-Terrorism and Counter-Extremism - Shanaah, Sadi (Terrorism and political violence, 2022)
The dominant academic narrative portrays British Muslim communities as alienated by counter-terrorism policies and consequently reluctant to cooperate with authorities by taking action against Islamist extremism. This article reassesses and nuances the “alienation narrative” with the use of unique data from three robust surveys of British Muslims. It finds that although a minority shows signs of alienation, most British Muslims are satisfied with and trust counter-terrorism policies as well as the government and the police. The level of willingness to take action against Islamist extremism is also high. The study confirms that aspects of alienation correlate with reduced willingness to take action against Islamist extremism, although they do not necessarily lead to disengagement.